Competence And Job Satisfaction: The Mediating Role Of Organizational Commitment From A Human Capital And Educational Management Perspective - Diah Putri Istiqamah; Hety Budiyanti; Tenri Sayu Puspitaningsi Dipoatmodjo; Uhud Darmawan Natsir; Zainal Ruma (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2026)
This study investigates the effect of employee competence on job satisfaction with organizational commitment as a mediating variable in the context of PT. Pelindo Terminal Petikemas New Makassar. Drawing on human capital theory, organizational behavior, and educational management perspectives, this research emphasizes competence as a strategic outcome of education and training that influences employee performance and satisfaction. A quantitative explanatory approach was employed using total sampling of 116 employees. Data were collected through a structured questionnaire and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results indicate that competence has a positive and significant effect on both job satisfaction (β = 0.360, p < 0.05) and organizational commitment (β = 0.699, p < 0.05). Organizational commitment also significantly influences job satisfaction (β = 0.208, p < 0.05) and partially mediates the relationship between competence and job satisfaction (VAF = 28%). The model explains 53.6% of the variance in job satisfaction, indicating moderate explanatory power. From an educational management perspective, the findings confirm that competence, developed through formal education and continuous training, plays a critical role in shaping employee commitment and satisfaction. This study highlights the importance of integrating education, human resource management, and economic strategies to enhance workforce quality and organizational sustainability.